How positive deviants helped in fighting the early phase of COVID-19 pandemic? A qualitative study exploring the roles of frontline health workers in Nepal - Rolina Dhital; Madhusudan Subedi; Pawan Kumar Hamal; Carmina Shrestha; Sandesh Bhusal; Reshika Rimal; Lovin Gopali; Richa Shah (Public Library of Science (PLoS), 2023)
Positive deviance is an approach wherein learnings from persons who fare better than their peers under similar circumstances are used to enable behavioral and social change. Such behaviors and solutions are likely affordable, acceptable, sustainable, and fit into the socio-cultural milieu. Despite the wide use of positive deviance in many public health programs and research, it has yet to be used to study frontline workers in the context of COVID-19. Therefore, this study aimed to explore the positive deviance traits among frontline health workers during the early days of the COVID-19 pandemic in Nepal. This qualitative study followed a grounded theory approach. The data was collected through in-depth interviews among the 17 identified participants representing different cadres of the health workforce, types of health facilities, and regions across Nepal purposively. The findings are structured around four major themes: challenges, finding solutions and innovations, positive lessons, and motivations. The personal challenges included fear and anxiety about the uncertainties. The professional challenges included stigma, infection control, and changing work style with the use of personal protective equipment. Despite the challenges, they managed available resources and innovated low-cost, technological, and practice-based solutions. They were able to reflect upon the positive lessons learned, such as self-sustainability, teamwork, and policy direction and research, and self-reflection of personal growth and patient care. The intrinsic motivation included their inherent value system, and the extrinsic motivation included appreciation and acknowledgment, family and social support, psychosocial support from peers, and support from higher authorities. This study provides insights into how the positive deviance approach can help identify the solution amid the most challenging circumstances, such as the COVID-19 pandemic in low-resource settings. However, more extensive studies are warranted to explore deeper into positive deviance and its long-term effects in bringing positive outcomes during the pandemic.